2010
DOI: 10.1007/s00421-010-1428-4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle ceramide content in man is higher in type I than type II fibers and not influenced by glycogen content

Abstract: Human muscle is studied during glycogen depletion and repletion to understand the influence of exercise and muscle glycogen on total ceramide content. In addition, fiber-type-specific ceramide storage is investigated. Ten healthy males (26.4 +/- 0.9 years, BMI 24.4 +/- 0.7 kg m(-2) and VO2max 57 +/- 2 mL O2 min(-1) kg(-1)) participated in the study. On the first day, one leg was glycogen-depleted (DL) by exhaustive intermittent exercise followed by low carbohydrate diet. Next day, in the overnight fasted condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Evidently, the available data on the effect of training on muscle bioactive lipid content are very inconsistent and an explanation for this is not readily apparent. We have previously demonstrated that ceramide content was higher in type I than type II muscle fibers in man [ 41 , 42 ] and therefore fiber type distribution, which often varies between lean and obese [ 28 , 43 ] and which in vastus lateralis demonstrate rather large heterogeneity [ 44 ], may explain some of this inconsistency. The total content of ceramide and DAG does not decrease significantly in response to endurance training; however, it could also be speculated that small nonsignificant changes may be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the available data on the effect of training on muscle bioactive lipid content are very inconsistent and an explanation for this is not readily apparent. We have previously demonstrated that ceramide content was higher in type I than type II muscle fibers in man [ 41 , 42 ] and therefore fiber type distribution, which often varies between lean and obese [ 28 , 43 ] and which in vastus lateralis demonstrate rather large heterogeneity [ 44 ], may explain some of this inconsistency. The total content of ceramide and DAG does not decrease significantly in response to endurance training; however, it could also be speculated that small nonsignificant changes may be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the fibers richer in glycogen contain the type 2 myosin heavy chain, 28 but some type 1 fibers may also be in this group. 29 Although this subject is rarely studied, Castillero et al 22 described a reduction in type 1 and type 2 myofibers in a rat model of adjuvant-induced arthritis, with a higher decrease in the fast twitch muscle fibers. Fink et al 30 described fiber type 2 atrophy in patients with osteoarthritis who submitted to knee prosthesis surgery.…”
Section: Discussionmentioning
confidence: 99%
“…All antibody dilutions and washes were conducted with immunobuffer (50 m m glycine, 0.25% BSA, 0.03% saponin and 0.05% sodium azide in PBS) as reported in Nordby et al . (). Slides were mounted with fluorescence mounting media (H‐4000; Vector Laboratories) and dried before imaging.…”
Section: Methodsmentioning
confidence: 97%